Aplikasi Informasi Kamar Kos di Wilayah Solo dengan Model Temu Kembali Berbahasa Sehari-hari - Marianto, Eka Sri; Hernawan Sulistyanto, S.T., M.T (2016)
Homestays are living in someone else's house to pay the rent within a specified period. In general, students, workers, migrants or tourists in search for a new dorm room, using conventional techniques, such as asking relatives, realtor boarding, or ask questions directly to the owners and board. To facilitate the search for boarding which is making a kos information applications through the web by using Indonesian daily (Information Retrieval) on search engines. The application contains search engines, admin login, see example image kos, kos description, price, phone number and a map of the location of boarding house owner. Methods of making these applications using SDLC (System Development Life Cycle). Application Information Kos Rooms in Solo region with Model Retrieval Net Daily use models VSM (Vector Space Model) capable of automatically searching the boarding information in the database. Based on the results of the questionnaire, this application can help users or prospective boarders in search of information dorm room, it can be seen from the percentage is at least 74% of users explained in a language easily, while the results of at most 89%, ie the web easier to use In making this application users can search for information kos quickly, saving time and costs, as well as more targeted information obtained